Estudo experimental da esclerose combinada subaguda de medula - Lima, Marcia Maria Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The B12 Vitamin deficiency in man, often associated with deficiency of intrinsic factor produced in the stomach, leading to several neurological and hematological disturbances. The best known alteration of the central nervous system is the demyelination and degeneration of the gracilis and cuneiform fascicles in the cervical spinal cord. This study aimed to try an experimental model of the disease, through total gastrectomy in rats. Animals were gastrectomized, submitted to oral polivitaminic supplementation, and 2-3 months later underwent nerve conduction studies. Electrical stimulation was done on the tail end, and electrical potentials were obtained at 3 points with equal distances from each other: near the anus (tail potential), lower spinal cord (lumbar potential) and the region of cervical spinal cord (cortical potential). The conduction velocity of the lower region of the spinal cord segment was named V1, the high spinal cord to the cortex was named V2 segment. After good quality records from 15 gastrectomized animals, the V1 and V2 segments were compared with data from 20 controls by the t Student test for independent samples, analysis of variance (ANOVA) and Tukey's multiple comparison test. Gastrectomized animals presented statistically significant reductions in the velocities for the V2 segment. The authors think they have obtained an experimental model of the disease in rats, which opens up broad prospects for therapeutic tests in the laboratory, with possibilities for future benefits to the man

A deficiência de vitamina B12 no ser humano, frequentemente associada a deficiência de fator intrínseco, produzido no estômago, leva a múltiplas alterações neurológicas e hematológicas. A mais conhecida alteração do sistema nervoso central é a desmielinização e degeneração dos fascículos grácil e cuneiforme da medula cervical. Este trabalho teve por objetivo tentar obter um modelo experimental da afecção, através da gastrectomia total em ratos. Animais foram gastrectomizados, submetidos à suplementação polivitamínica via oral, e 2 a 3 meses depois submetidos a estudos de condução nervosa, com estímulos elétricos na extremidade da cauda, e captação de potenciais elétricos em 3 pontos, com distâncias iguais entre si: próximo ao ânus (potencial caudal), região inferior da coluna (potencial lombar) e região da protuberância cervical (potencial cortical). A velocidade de condução pela região inferior da medula espinhal foi denominada segmento V1, pela região torácica alta e cervical até o córtex, segmento V2. Após obtenções de registros de boa qualidade técnica em 15 gastrectomizados, os segmentos V1 e V2 foram comparados com dados de 20 controles pelo teste t de Student para amostras independentes, análise de variância (ANOVA) e teste de comparação múltipla de Tukey. Os animais gastrectomizados apresentaram reduções de velocidades estatisticamente significativas para o segmento V2. Os autores pensam ter conseguido modelo experimental da afecção em ratos, o que abre amplas perspectivas para testes terapêuticos em laboratório, com possibilidades para benefícios futuros ao homem
Experimental model of the subacute combined sclerosis of the spinal cord
Keywords: Gastrectomia; Estomago - Cirurgia; Medula espinhal - Doenças; Deficiência de vitamina B 12; Vitamina B12; Spinal cord - Diseases